Gluten-free Diet Reduces the Risk of Irritable Bowel Syndrome: A Mendelian Randomization Analysis - Sun, Yuhao; Chen, Xuejie; Wang, Shuyang; Deng, Minzi; Xie, Ying; Wang, Xiaoyan; Chen, Jie; Hesketh, Therese (Frontiers in Genetics, 2021)
Background: Patients with irritable bowel syndrome (IBS) have been observed that could benefit from a gluten-free diet (GFD), but whether it is a cause of IBS remains controversial. We aim at exploring the causal relationship between gluten intake and IBS within Mendelian randomization (MR) design. Methods: We conducted a two-sample Mendelian randomization (MR) and selected single nucleotide polymorphisms (SNPs) associated with GFD as instrumental variables (IVs). SNPs and genetic associations with GFD and IBS were obtained from the latest Genome-Wide Association Studies (GWAS) in Europeans (GFD: cases: 1,376; controls: 63,573; IBS: cases:1,121; controls: 360,073). We performed inverse variance weighted (IVW) as the primary method with several sensitivity analyses like MR-Egger and MR-PRESSO for quality control. The above analyses were re-run using another large dataset of IBS, as well as changing the p-value threshold when screening IVs, to verify the stability of the results. Results: The final estimate indicated significant causal association (per 1 copy of effect allele predicted log odds ratio (OR) change in GFD intake: OR=0.97, 95% CI 0.96 to 0.99, p<0.01) without heterogeneity statistically (Q=2.48, p=0.78) nor horizontal pleiotropy biasing the causality (p=0.92). Consistent results were found in validation analyses. Results of MR Steiger directionality test indicated the accuracy of our estimate of the causal direction (Steiger p < 0.001). Conclusion: GFD might be a protective factor of IBS. Therefore, we suggest taking a diet of lower gluten intake into account in IBS prevention and clinical practice.